2005
DOI: 10.1007/s00441-004-1065-5
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I stimulates cell proliferation in the outer layer of Hertwig?s epithelial root sheath and elongation of the tooth root in mouse molars in vitro

Abstract: To elucidate the mechanism of root formation in tooth development, we examined the role of insulin-like growth factor I (IGF-I) on early root formation in mandibular first molar teeth from 5-day-old mice. Immunohistochemistry revealed the specific localization of the IGF-I receptor in Hertwig's epithelial root sheath (HERS) in the tooth root. The effect of IGF-I on root development, especially on HERS, was subsequently examined in vitro. The control culture showed normal development of HERS and the periodontiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 16 publications
3
61
0
Order By: Relevance
“…In addition to the signaling molecules mentioned above, studies have shown that IGF1 and HGF may also be involved in regulating root formation (Fujiwara et al, 2005;Sakuraba et al, 2012), although their precise function in regulating epithelial or mesenchymal cells is yet to be elucidated. Nonetheless, taking all of these studies together, we are beginning to understand the complex signaling network that regulates epithelial-mesenchymal interactions during root formation (summarized in Fig.…”
Section: Fgf and Hh Signalingmentioning
confidence: 99%
“…In addition to the signaling molecules mentioned above, studies have shown that IGF1 and HGF may also be involved in regulating root formation (Fujiwara et al, 2005;Sakuraba et al, 2012), although their precise function in regulating epithelial or mesenchymal cells is yet to be elucidated. Nonetheless, taking all of these studies together, we are beginning to understand the complex signaling network that regulates epithelial-mesenchymal interactions during root formation (summarized in Fig.…”
Section: Fgf and Hh Signalingmentioning
confidence: 99%
“…To label the mutant incisors growing under the kidney capsules, 1 mg/100 g (body weight) BrdU (Sigma-Aldrich, St Louis, MO, USA) was injected into the abdominal cavity of recipient mice (those transplanted with the mutant incisor germs), which were sacrificed 2 hours later, at which point the incisor immunostaining was carried out. In vitro cultures for observing root development of mouse molars were performed as previously described (Fujiwara et al, 2005). Explants from PN d3 and d5 mice were incubated for 1 day and then washed with Hanks' balanced salt solution in the presence of BrdU (0.5 mg/ml for 3 hours), embedded in paraffin, and serially sectioned into 5 m sections.…”
Section: Cell Proliferation Assaysmentioning
confidence: 99%
“…Studies performed from the benchtop to the clinic have provided exciting possibilities for BMP-2 and IGF-1 to stimulate periodontal tissue repair (Vainio, et al, 1993;Yamaguchi, 1995;King and Hughes, 2001;Xu, et al, 2003;Fujiwara, et al, 2005;Ripamonti, et al, 2005;Popowics, et al, 2005;Soares, et al, 2005;Kaigler, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…During the past twenty years, many investigators have demonstrated the anabolic effects of locally application of many growth factors (GFs) on the promotion of periodontal attachment structures, namely alveolar bone, periodontal ligament (PDL) and tooth root cementum (Giannobile, 1996;King and Hughes, 2001;King and Cochran, 2002;Zhao, et al, 2002;Fujiwara, et al, 2005;Kaigler, et al, 2006). The mechanisms of GFs that control and enhance periodontal regeneration capacity are poorly understood; however, some studies have shown that the association of different GFs would enhance their activity in a synergistic manner compared to the activity of a single GF (Lynch, et al, 1991a(Lynch, et al, , 1991bShih, et al, 1996;Howell, et al, 1997;Zaman, et al, 1999;Ripamonti, et al, 2001;Puleo, 2004a, 2004b).…”
Section: Introductionmentioning
confidence: 99%